Arab journalistic translators’ familiarity with the Arabic language academy’s terminology work of Arabicization - Ghada Saeed Salman; Idris Mansor (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper aims to investigate the stances and perceptions of Arab journalistic translators about the terminology work of Arabicization and to what extent they are familiar with the Arabicized terms, which are proposed by the Arabic Language Academy (ALA) in the Arab region. The Arabicization task has been concertedly shouldered by language academies in several Arab countries, such as Cairo, Iraq, and Jordan. In this study, Arab journalistic translators’ attitudes, familiarity, and employment of the proposed Arabicized termsin journalistic translation have been investigated. In this study, the adopted methodology follows the quantitative approach to collect and analyse the data of a small-scale survey among Arab journalists and translators in various media outlets in the Arab region. The respondents of the conducted survey included Arab journalists, journalistic translators, script editors, and interpreters at Arab press agencies in several Arab countries, including Jordan, Qatar, and Egypt. According to the survey findings, the proposed Arabicized terms by the Arabic Language Academy are not broadly circulated among Arab journalists and translators in the Arab press. Moreover, the results confirmed that Arab journalistic translators are not completely familiar with the academy’s Arabicized terminologies. Therefore, they do not use them in English-Arabic journalistic translation. To enhance the ALA’s terminology work of Arabicization, more effective endeavours should be directed towards circulating the academy’s Arabicized terminology among journalistic translators in the media sector in the Arab region through establishing cooperation and coordination channels between the academy and the Arab press agencies.